2004
DOI: 10.1002/pola.20496
|View full text |Cite
|
Sign up to set email alerts
|

Single‐electron‐transfer/degenerative‐chain‐transfer mediated living radical polymerization of vinyl chloride catalyzed by thiourea dioxide/octyl viologen in water/tetrahydrofuran at 25 °C

Abstract: The single‐electron‐transfer/degenerative‐chain‐transfer mediated living radical polymerization (SET–DTLRP) of vinyl chloride (VC) in H2O/tetrahydrofuran at 25 °C catalyzed by thiourea dioxide [(NH2)2CSO2] is reported. This polymerization occurs only in the presence of a basic sodium bicarbonate (NaHCO3) buffer and the electron‐transfer cocatalyst octyl viologen. The resulting poly(vinyl chloride) (PVC) has a number‐average molecular weight of 1500–7000 and a weight‐average molecular weight/number‐average mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…The single‐electron‐transfer/degenerative‐chain‐transfer mediated living radical polymerization of vinyl chloride in water/tetrahydrofuran catalyzed by thiourea dioxide has been studied by Percec and co‐workers 8a. They have shown that polymerization proceeds only in the presence of NaHCO 3 and co‐catalyst octyl viologen (OV 2+ ).…”
Section: Stability and Reactivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The single‐electron‐transfer/degenerative‐chain‐transfer mediated living radical polymerization of vinyl chloride in water/tetrahydrofuran catalyzed by thiourea dioxide has been studied by Percec and co‐workers 8a. They have shown that polymerization proceeds only in the presence of NaHCO 3 and co‐catalyst octyl viologen (OV 2+ ).…”
Section: Stability and Reactivitymentioning
confidence: 99%
“…The reason is that contrary to thiourea dioxide, a single‐electron‐transfer reductant—sulfur dioxide anion radical—is produced by the dissociation of dianion S 2 O 4 2− directly (to form SO 2 − from sulfoxylate, the presence of an oxidizing agent is required). The other reason of relatively low effectiveness of TDO is the possible side reactions caused by the sulfoxylate anion—the product of decomposition of thiourea dioxide 8a. Indeed, sulfoxylate can reduce OV 2+ to the neutral octyl viologen, which is an extremely strong reductant.…”
Section: Stability and Reactivitymentioning
confidence: 99%
“…On the other hand a one-electron reduction [52,53] of the chloramine by electron rich aromatic moieties, leading to the formation of a free N-radical [5456], which, in turn, captures hydrogen atoms from –OH groups in phenolic SDG moieties [57], cannot be completely ruled out (not shown). Scheme 2 indicates the proposed mechanism of SDG radioprotection.…”
Section: Resultsmentioning
confidence: 99%
“…At 130 °C in o ‐dichlorobenzene, the LRP of VC initiated by iodide‐containing molecules could be achieved up to ∼20% conversion through single‐electron transfer (SET) activation and degenerative chain‐transfer (DT), the combination of which was subsequently termed single‐electron transfer degenerative transfer/living radical polymerization (SET‐DTLRP). Later, nonmetallic SET activators such as SO 2•− derived from the aqueous phase decomposition of sodium diothionite5–7 or thiourea/octyl viologen8 were determined to mediate effective aqueous SET‐DTLRP of VC initiated by iodoform or methylene iodide9 at ambient temperatures. Application of this technique allowed for the synthesis of ultrahigh molecular weight PVC free of structural defects and that exhibited a high degree of syndiotacticity and commensurately elevated T g 10.…”
Section: Introductionmentioning
confidence: 99%